2021
DOI: 10.1002/jimd.12427
|View full text |Cite
|
Sign up to set email alerts
|

Mechano‐energetic aspects of Barth syndrome

Abstract: Energy‐demanding organs like the heart are strongly dependent on oxidative phosphorylation in mitochondria. Oxidative phosphorylation is governed by the respiratory chain located in the inner mitochondrial membrane. The inner mitochondrial membrane is the only cellular membrane with significant amounts of the phospholipid cardiolipin, and cardiolipin was found to directly interact with a number of essential protein complexes, including respiratory chain complexes I to V. An inherited defect in the biogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 204 publications
0
9
0
Order By: Relevance
“…This raises the important question as to why stimulating myocardial PDH activity would fail to yield benefit in TazKD mice, considering numerous other cardiac pathologies are corrected by such a metabolic strategy? We posit that the persistent destabilization of ETC supercomplexes and reduced ETC complex activity coupled with consequent elevations of mitochondrial reactive oxygen species and oxidative stress (10,11,(30)(31)(32), likely supersede intermediary metabolism defects present in BTHS. This may explain the failure of DCA treatment to attenuate the LV hypertrophic remodeling in TazKD mice despite an improvement of myocardial glucose oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the important question as to why stimulating myocardial PDH activity would fail to yield benefit in TazKD mice, considering numerous other cardiac pathologies are corrected by such a metabolic strategy? We posit that the persistent destabilization of ETC supercomplexes and reduced ETC complex activity coupled with consequent elevations of mitochondrial reactive oxygen species and oxidative stress (10,11,(30)(31)(32), likely supersede intermediary metabolism defects present in BTHS. This may explain the failure of DCA treatment to attenuate the LV hypertrophic remodeling in TazKD mice despite an improvement of myocardial glucose oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TAFAZZIN deficiency is associated with an impairment of mitochondrial respiratory capacity and ATP production, which to date, has largely been attributed to destabilization of the IMM electron transport chain (ETC) ( 18 ). Normal production of ATP in healthy mitochondria involves the oxidation of fatty acids, glucose, ketones, and amino acids to produce acetyl-CoA, which enters the Krebs cycle resulting in the generation of reducing equivalents (i.e., NADH and FADH 2 ) by its 4 dehydrogenase enzymes.…”
Section: Mitochondrial Respiratory Abnormalities In Barth Syndromementioning
confidence: 99%
“…Key features of each of the different model systems ranging from yeast to fruit fly, zebrafish, mice, and induced pluripotent stem cells, and their relevance to Barth syndrome are discussed. The next paper in line by Dudek and Maack 10 deals with the mechano‐energetic aspects of Barth syndrome induced by the impairment in cardiolipin synthesis and remodeling. Special attention is paid to calcium which plays a central role during excitation‐contraction with calcium released from the sarcoplasmic reticulum driving sarcomere contraction.…”
mentioning
confidence: 99%
“…Special attention is paid to calcium which plays a central role during excitation‐contraction with calcium released from the sarcoplasmic reticulum driving sarcomere contraction. Mitochondria are key players in calcium homeostasis as mediated by the mitochondrial calcium uniporter (MCU) complex made up of several proteins and it has been shown that cardiolipin interacts with several of the regulatory subunits of the MCU‐complex including MICU1 and MICU2 with important ramifications for Barth syndrome 10 . The subsequent contribution by Bozelli and Epand 11 focuses on the consequences of the defect in cardiolipin metabolism observed in Barth syndrome on other lipids, notably plasmalogens which constitute a special class of lipid species characterized by the presence of an ether/vinyl‐ether rather than an ester bond at the sn ‐1 position of the glycerol backbone.…”
mentioning
confidence: 99%
See 1 more Smart Citation